Applying of Design Failure Models and Effects Analysis (DFMEA) to bank account operations using Artificial Neural Networks (ANN) An applied study on the Syrian Real Estate Bank - Tishreen Branch// - بسام حسن زاهر; غسان محمد دخول (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aimed to applying the concept of failure design models and effects analysis (DFMEA) to banking operations in the bank accounts department of the Syrian Real Estate Bank, Tishreen Branch, by studying the performance requirements, how and areas of its application, the work mechanism and the work team. Where the team was formed, the work mechanism was applied, the scenarios that affect operations and activities were identified, and the degree of risk for each scenario was determined. Then, a model of the degree of risk affecting the performance of banking operations was built using artificial neural networks (ANN), and this model was applied to the data obtained from the application of failure design models and effects analysis. The research found that the application of failure design and effects analysis (DFMEA) models using artificial neural networks (ANN), affects the original and revised severity degrees affecting the performance of banking operations